Students' Perceptions of Learning Management Using PlantNet Application-Assisted Teaching Materials - Yani Astuti; Ayit Irpani; Silmi Amrullah; Deden Heryanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to analyze students' perceptions of the use of teaching materials assisted by the PlantNet application in science learning, especially in plant classification material. This study uses a descriptive quantitative method with data collection through a questionnaire involving 180 students at the MTs level. Perception measurement is carried out by assessing several dimensions, namely ease of use, involvement and motivation to learn, understanding of the material, student satisfaction with learning, and utilization of the application outside the classroom. Data analysis is carried out by calculating the average score and percentage of each dimension. The results showed that students' perceptions of the use of PlantNet were very positive, with an overall average score of 4.1 on a scale of 1–5. As many as 85% of students stated that this application was easy to use, while 82% of students felt more motivated and involved in the learning process. In addition, 78% of students stated that the use of PlantNet helped their understanding of plant classification, with an average score of 4.0 for the dimension of understanding the material. This application was also considered satisfactory by 80% of students, although the level of utilization outside the classroom was lower, with an average score of 3.8. The conclusion of this study is that the PlantNet application is effective as a technology-assisted teaching material, able to increase students' motivation and understanding through contextual and interactive learning. However, further integration is needed in field project activities so that this application can be optimally utilized outside the classroom. The recommendation for teachers is to integrate PlantNet with project-based learning methods to maximize its positive impact on science learning.